1994
DOI: 10.1182/blood.v83.7.1871.1871
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the chromosomal translocation t(11;14) by polymerase chain reaction in mantle cell lymphomas

Abstract: The t(11;14)(q13;q32) and its molecular counterpart, BCL1 rearrangement, are consistent features of mantle cell lymphoma (MCL). Rearrangement is thought to deregulate the nearby CCND1 (BCL1/PRAD1) proto-oncogene, a member of the cyclin G1 gene family, and thereby to contribute to tumorigenesis. We and others have previously shown that the BCL1 locus is rearranged in 55% to 60% of MCL patients and that, on chromosome 11, more than 80% of the breakpoints are localized within a 1-kbp DNA segment known as the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(68 citation statements)
references
References 24 publications
6
62
0
Order By: Relevance
“…(B) Hybridization of the PCR amplification products corresponding to lanes 1-7 with a 32 P-dATP-labelled oligonucleotide probe (P4-11). Secondary bands of higher MW in lanes 4 and 5, that hybridize, represent PCR amplification products of bcl-1 with a J H 6 downstream of the J H gene (usually J H 4) that forms the junction, and observation also underscored by Rimokh et al (1994). probe (P4-11; 5 0 -TTTGGATAAAGGCGAGGAGC-3 0 ) internal to the primers used for the amplification reactions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(B) Hybridization of the PCR amplification products corresponding to lanes 1-7 with a 32 P-dATP-labelled oligonucleotide probe (P4-11). Secondary bands of higher MW in lanes 4 and 5, that hybridize, represent PCR amplification products of bcl-1 with a J H 6 downstream of the J H gene (usually J H 4) that forms the junction, and observation also underscored by Rimokh et al (1994). probe (P4-11; 5 0 -TTTGGATAAAGGCGAGGAGC-3 0 ) internal to the primers used for the amplification reactions.…”
Section: Methodsmentioning
confidence: 99%
“…The identifiable D gene sequences were found to bear homology to DLR3, DM (Both DM1 and DM5) and DIR5 germline D genes (Table I). The analysis of the published junctional sequences yielded homology to germline D genes in 2/8 cases (Rimokh et al, 1994). Homology to germline D genes with a maximum of two base changes/deletions intervening was 10, 10 and nine nucleotides for samples 1406, 1413 and 3052, respectively (Table I).…”
Section: Junctional Sequences Of the Bcl-1 (Mtc)/j H Fusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclin D1 overexpression may be detected by paraffin section immunohistochemistry, but this is difficult both to accomplish and to interpret owing to the intense antigen retrieval necessary to optimize cyclin D1 immunoreactivity. The t(11;14)(q13;q32) has also been detected using polymerase chain reaction (PCR) and primers for a consensus immunoglobulin heavy chain joining region on chromosome 14 and a portion of the major translocation cluster (MTC) region on chromosome 11 (Williams et al, the wide variation in breakpoints along the cyclin D1 locus, the sensitivity of this technique ranges between only 27% and 57% (Rimokh et al, 1994;Luthra et al, 1995;Segal & Maiese, 1996;Chibbar et al, 1998).…”
mentioning
confidence: 99%
“…34 Upregulation of CCND1 has been described in B-cell chronic lymphocytic leukaemia 35 and mantle cell lymphoma 36 as a consequence of a t(11;14)(q13;q32) translocation, leading to the juxtaposition of the CCND1 gene at 11q13 with the promoter region of the IgH gene at 14q32. 37,38 Increased CCND1 gene expression is also present in other B-cell lymphomas. [18][19][20] In this study, CCND1 protein was found to be expressed in a large proportion of PCBCL cases.…”
Section: Casementioning
confidence: 99%